2013
DOI: 10.1080/09670262.2013.860482
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic position and phenotypic changes of a Chlorella-like alga during 5-year microcosm culture

Abstract: Recent phylogenetic studies of Chlorella-like algae revealed that this group has diversified into free-living and endosymbiotic niches, the latter within protists and invertebrate organisms. Our previous studies using a long-term culture composed of an alga (Chlorella vulgaris, rDNA sequence unknown), a bacterium (Escherichia coli) and a ciliate (Tetrahymena thermophila), suggested that some clones in the algal population developed an endosymbiotic ability with T. thermophila while others developed an ectosymb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In order to analyse the early evolutionary process of endosymbiosis between autotrophic and heterotrophic organisms, we developed an experimental ecosystem model, the CET microcosm, composed of a green alga (Micractinium sp., formerly described as Chlorella vulgaris), a bacterium (Escherichia coli) and a ciliate (Tetrahymena thermophila) Germond et al, 2013a). During the 3-year culture of this microcosm without transfer, we observed that ciliate cells harbouring living algal cells appeared at a frequency of up to 80-90% throughout the experiment .…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…In order to analyse the early evolutionary process of endosymbiosis between autotrophic and heterotrophic organisms, we developed an experimental ecosystem model, the CET microcosm, composed of a green alga (Micractinium sp., formerly described as Chlorella vulgaris), a bacterium (Escherichia coli) and a ciliate (Tetrahymena thermophila) Germond et al, 2013a). During the 3-year culture of this microcosm without transfer, we observed that ciliate cells harbouring living algal cells appeared at a frequency of up to 80-90% throughout the experiment .…”
Section: Introductionmentioning
confidence: 73%
“…and the ciliate (T. thermophila), and that at least some algal clones evolved a particular phenotype that benefits the ciliate. Genetic studies based on sequences of 18S and ITS regions (2700 bp length) showed no differences between the ancestral strains and 12 algal clones isolated from long-term microcosms (Germond et al, 2013a). Further studies using two algal clones (SC9-1 and SC10-2), isolated from within Tetrahymena cells, revealed that these clones released higher concentrations of glycerol and sucrose at pH 7.2 when compared with the ancestral strain at the same pH (Germond et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations